Structure affinity relationship and docking studies of flavonoids as substrates of multidrug-resistant associated protein 2 (MRP2) in MDCK/MRP2 cells. (1st September 2019) - Fang, Yajing; Cao, Weiwei; Liang, Fuqiang; Xia, Mengmeng; Pan, Siyi; Xu, Xiaoyun
Highlights: MRP2 was stably expressed in MDCK/MRP2 cells. 8 of 35 flavonoids were identified as substrates of MRP2 in MDCK/MRP2 cells. SAR and docking were done for structure requirements of flavonoid substrates. 3, 5, 6, 3′-OH, 4′-OCH3 favoured but 8, 3′-OCH3, 2′, 4′, 5′-OH disfavoured for MRP2 affinity. Abstract: This study was aimed to determine the relationship of flavonoid structures to their affinity for an important efflux transporter, multidrug-resistant associated protein 2 (MRP2). The cellular uptake (CU) of 35 flavonoids was investigated in MRP2 overexpression MDCK/MRP2 cells. Resulting data identified 8 flavonoids as MRP2 substrates based on their high CUMK with MK-571 in MDCK/MRP2 cells. Also, three substrates showed better CUMD in MDCK cells than did CUMRP in MDCK/MRP2 cells. Docking analyses showed a good correlation (R = 0.926, p  = 0.003) between efflux-fold of flavonoid substrates and their docking S_scoring with the MRP2 model, indicating consistency between in silico and in vitro approaches. A structure affinity relationship (SAR) study indicated that 3-OH, 5-OH, 6-OH, 3′-OH, and 4′-OCH3 substituents were favourable while, 8-OCH3, 2′-OH, 3′-OCH3, 4′-OH and 5′-OH were unfavourable for flavonoid affinity to MRP2. Our study provides valuable information for dietary application of flavonoids with specific structures for high absorption.